Model Aplikasi E-Voting Berbasis WEB Pada Pemilihan Ketua Badan Eksekutif Mahasiswa - Siti Hardianti; Yulia Yudhihartanti (STMIK Banjarbaru, 2015)
The development of information technology has brought great changes to people, including to carry out voting. The use of computer technology in the implementation of voting is known as electronic voting or commonly known as e-voting. Student Executive Board (BEM) STMIK Banjarbaru is an organization owned by a university or high school functioned as a forum for representatives of all students STMIK Banjarbaru. Student Executive Board (BEM) STMIK this Banjarbaru certainly have members who are not the least, during this process of selecting new head diruang scope of the Student Representative Council (BPM) is still done manually.Election of Chairman STMIK Banjarbaru BEM can be overcome by utilizing Computer Science and Information Technology (ICT) that electronic voting (e-voting) or build an application of e-voting to carry out the selection head is that it takes time and place of voters (students) in the election can be balanced and can increase the number of voters. One way that is easy and efficient in the development of e-voting election is to use a client-server architecture and algorithms pesentase in the graph.From the research that has been done to implement the e-voting system, then the conclusion is obtained that can increase the number of voters, smoothed data management, reduce the risk of loss of voice, reducing the budget, as well as speeding up the counting.Key Word : Applications Web-Based E-Voting in the Election of the Chairman of the BEM STMIK Banjarbaru